Selection on Moral Hazard in Health Insurance - Einav, Liran; Finkelstein, Amy; Ryan, Stephen P; Schrimpf, Paul; Cullen, Mark R (American Economic Review, 2013)
We use employee-level panel data from a single firm to explore the possibility that individuals may select insurance coverage in part based on their anticipated behavioral ("moral hazard") response to insurance, a phenomenon we label "selection on moral hazard." Using a model of plan choice and medical utilization, we present evidence of heterogeneous moral hazard as well as selection on it, and explore some of its implications. For example, we show that, at least in our context, abstracting from selection on moral hazard could lead to over-estimates of the spending reduction associated with introducing a high-deductible health insurance option.